Literasi Pajak Pertambahan Nilai (PPN) kepada UMKM Salad Buah Mommy Q&A di Kota Cilegon - Salza Rahmawati; Sandy Ikhwan Balasih (Indo Publishing, 2026)
This Community Service Program was carried out at the Mommy Q&A Fruit Salad Small Micro, Medium, Enterprises (SMME) in Cilegon City. However, the Mommy Q&A fruit Salad Business Owners were more focusedon production and sales activities and did not yet understand tax obligations well, especially regarding Value Added Tax (VAT). This is because tax management is a complex matter and requires specialized knowledge. This activity aims to improve the understanding and tax literacy of Mommy Q&A Fruit Salad Small Micro, Medium, Enterprises (SMME) actors in Cilegon City through educational programs, training, and mentoring. The method used in this study was a descriptive qualitative method with data collection techniques in the form of direct observation of Small Micro, Medium, Enterprises (SMME) regarding the problems that occurred, as well as through an educational, participatory, and applied approach in addressing existing problems. The result of this activity